THE ROLE OF PEDAGOGICAL SKILLS IN DETERMINING THE STUDENTS 'TALENT AND DEVELOPING THEIR TALENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the role and importance of pedagogical skills in the identification and development of gifted students of school age, and ways to properly organize education and upbringing.